1976
DOI: 10.1677/joe.0.0710021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bilateral Adrenalectomy and Corticosteroid Therapy on the Secretion of Corticotrophin-Releasing Factor Activity From the Hypothalamus of the Rat in Vitro

Abstract: The rat hypothalamus in vitro preparation was used to investigate the effect of bilateral adrenalectomy, with and without replacement therapy, on the release of corticotrophin-releasing factor(CRF). Corticotrophin-releasing factor was estimated using 48 h basal hypothalamic lesioned assay rats and corticosterone production of excised adrenals was used as the end point. Bilateral adrenalectomy resulted in depletion of hypothalamic CRF content within the first 2 h after the operation but this effect was prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Sl-EP has been shown to suppress ACTH and cortisol levels in normal subject (54) and to inhibit both corticotropin-releasing bioactivity (CRB) and iCRH secretion in vitro (55,56 Our results suggesting the presence of a long glucocorticoid-mediated negative feedback loop are consistent with studies conducted with similar or different experimental paradigms. In this regard, it has been shown that CRB content of the hypothalamus and the sensitivity of CRB secretion to various stimuli are increased after adrenalectomy and both effects are reversed by glucocorticoid administration (29,30,33,34). Furthermore, stress-induced and basal CRB content of the hypothalamus and the median eminence are suppressed by glucocorticoid administration (24)(25)(26) or by DEX implants in the median eminence (66).…”
Section: Resultsmentioning
confidence: 99%
“…Sl-EP has been shown to suppress ACTH and cortisol levels in normal subject (54) and to inhibit both corticotropin-releasing bioactivity (CRB) and iCRH secretion in vitro (55,56 Our results suggesting the presence of a long glucocorticoid-mediated negative feedback loop are consistent with studies conducted with similar or different experimental paradigms. In this regard, it has been shown that CRB content of the hypothalamus and the sensitivity of CRB secretion to various stimuli are increased after adrenalectomy and both effects are reversed by glucocorticoid administration (29,30,33,34). Furthermore, stress-induced and basal CRB content of the hypothalamus and the median eminence are suppressed by glucocorticoid administration (24)(25)(26) or by DEX implants in the median eminence (66).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of a silent period in our experiments may be because nonstress and stress-induced ACTH secretion are dissociated on the basis of sensitivity to negative corticosteroid feedback effects (10)(11)(12). In more recent experiments, corticosteroid feedback mechanisms were investigated at the hypothalamic level with the technique of the rat hypothalamus in vitro (18,19); both fast and delayed feedback effects on secretion of corticotropin-releasing factor were demonstrated with doses of corticosteroids within, or near, the physiologic range. The results suggested that the fast feedback mechanism acted via the inhibition of release, whereas the delayed feedback mechanism acted via inhibition of both synthesis and release.…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoid pretreatment inhibited plasma ACTH responses to stress to a significantly greater extent Hillhouse and Jones, 1976;Plotsky and Vale, 1984;Plotsky et al, 1986;Plotsky and Sawchenko, 1987;Sawchenko, 1987a,b;Owens et al, 1990;Imaki et al, 1991). Indeed, this process is considered as a basis for delayed glucocorticoid negative-feedback effects (see Dallman et al, 1992).…”
Section: Discussionmentioning
confidence: 98%